Financial Performance Analysis of Regency and City Governments in North Sumatera - Yosephine Magdalena Sipahutar; Irawan Irawan; Tia Novira Sucipto (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study analyzes the financial performance of local governments in North Sumatra— specifically Medan City, Binjai City, Toba Regency, Simalungun Regency, and Deli Serdang Regency—based on the independence, effectiveness, and efficiency ratios of locally generated revenue (PAD) for the period 2020–2024. Using a descriptive quantitative method with data sourced from the Regional Budget Realization Reports, the findings indicate that fiscal independence across all regions remains low to very low, although several areas show a gradual upward trend. The PAD effectiveness ratio generally falls within the effective to highly effective categories, reflecting the regions’ ability to meet revenue targets. However, the efficiency ratio indicates inefficiency in most years, suggesting that regional spending is not aligned with the capacity of PAD. Overall, the study highlights the need to strengthen PAD and improve budget efficiency in order to enhance the financial performance of local governments.